2017
DOI: 10.3389/fphar.2017.00002
|View full text |Cite
|
Sign up to set email alerts
|

β-Caryophyllene/Hydroxypropyl-β-Cyclodextrin Inclusion Complex Improves Cognitive Deficits in Rats with Vascular Dementia through the Cannabinoid Receptor Type 2 -Mediated Pathway

Abstract: This work was conducted to prepare β-caryophyllene-hydroxypropyl-β-cyclodextrin inclusion complex (HPβCD/BCP) and investigate its effects and mechanisms on cognitive deficits in vascular dementia (VD) rats. First, HPβCD/BCP was prepared, optimized, characterized, and evaluated. HPβCD/BCP and AM630 were then administered to VD rats to upregulate and downregulate the cannabinoid receptor type 2 (CB2). Results showed that HPβCD/BCP can significantly increase the bioavailability of BCP. Through the Morris water ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…This pathway is involved in the regulation of cell growth, proliferation and differentiation through a series of responses and is a classic anti-apoptotic and pro-survival signal transduction pathway. In recent years, studies have shown that the CB 2 R agonist exhibits a neuroprotective effect in the CNS by activating the PI3K/Akt signaling pathway [ 42 ], which reduces cognitive impairment, increases cerebral blood flow, and inhibits neuronal apoptosis in an animal model of VD [ 43 ]. Akt is a common upstream regulator of both mTOR and NF-κB pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is involved in the regulation of cell growth, proliferation and differentiation through a series of responses and is a classic anti-apoptotic and pro-survival signal transduction pathway. In recent years, studies have shown that the CB 2 R agonist exhibits a neuroprotective effect in the CNS by activating the PI3K/Akt signaling pathway [ 42 ], which reduces cognitive impairment, increases cerebral blood flow, and inhibits neuronal apoptosis in an animal model of VD [ 43 ]. Akt is a common upstream regulator of both mTOR and NF-κB pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Di Sotto et al [ 242 ] also highlighted that the lipid-to-drug ratio should be considered as a critical parameter for enabling β-caryophyllene release from a lipid-based nanocarrier, in order to avoid the substance condensing effect on the bilayer, and for increasing its cytotoxic power in cancer cells. According to previous pharmaceutical studies [ 246 , 247 , 248 , 249 ], this evidence suggests that improving the bioavailability of these sesquiterpenes is an important goal for exploiting their pharmacological potential and strengthens the need of developing optimized delivery formulations.…”
Section: Caryophyllane Sesquiterpenes In Cancer Chemopreventionmentioning
confidence: 96%
“…Machado et al [81] have recently reviewed the neuroprotective perspective of this natural product. β-Caryophyllene appears to act as a neuroprotective agent by controlling inflammation and oxidative stress as well as various effects on cannabinoid receptor 2 (CB2) [80][81][82]. In a vascular dementia rat model study, Lou et al [82] reported that β-caryophyllene-hydroxypropyl-β-cyclodextrin inclusion complex could alleviate cognitive deficits by increasing the expression of CB2 in the brain, along with the expression levels of phosphoinositide 3-kinase (PI3K) and protein kinase B (Akt).…”
Section: β-Caryophyllenementioning
confidence: 99%
“…β-Caryophyllene appears to act as a neuroprotective agent by controlling inflammation and oxidative stress as well as various effects on cannabinoid receptor 2 (CB2) [80][81][82]. In a vascular dementia rat model study, Lou et al [82] reported that β-caryophyllene-hydroxypropyl-β-cyclodextrin inclusion complex could alleviate cognitive deficits by increasing the expression of CB2 in the brain, along with the expression levels of phosphoinositide 3-kinase (PI3K) and protein kinase B (Akt). β-Caryophyllene also acted as agonist for CB2 and PPAR-α receptors in an animal hypoperfusion-reperfusion model of oxidative stress, and modulated activation of the endocannabinoid system and lipoperoxidation as well ▶ Table 2 Continued…”
Section: β-Caryophyllenementioning
confidence: 99%